Guidance on breastfeeding in the prenatal period offered to pregnant women: A literature review (International Seven Journal of Health Research, 2023)
Introduction: Breastfeeding is the best way to provide the ideal food for the healthy growth and development of newborns. However, it is observed that there is a latent tendency to early weaning and mixed breastfeeding, making this a public health problem. Objective: The objective of this work is to clarify the importance of exclusive breastfeeding, as well as the role of the health professional to promote breastfeeding and present WHO data on this topic. Methodology: This is a descriptive bibliographic review work that had as theoretical basis articles published in the period from 2013 to 2023, where the most important ones were selected to be discussed here. Results: According to the information covered in the articles, exclusive breastfeeding is very important for the baby's health, there is also a lack of adequate transfer of information about this importance to mothers in the prenatal period. Conclusion: With the accomplishment of the present study it became evident the fact that despite the recommendations of the World Health Organization, especially with regard to exclusive breastfeeding, the reality in Brazil is far from reaching the minimum numbers of pregnant women who choose to breastfeed after the gestational period.